Interplay of Energetics and ER Stress Exacerbates Alzheimer's Amyloid-β (Aβ) Toxicity in Yeast - Chen, Xin; Bisschops, Markus M. M.; Agarwal, Nisha R.; Ji, Boyang; Shanmugavel, Kumaravel P.; Petranovic, Dina (Frontiers in Molecular Neuroscience, 2017)
Alzheimer’s disease (AD) is a progressive neurodegeneration. Oligomers of Amyloid-β peptides (Aβ) are thought to play a pivotal role in AD pathogenesis, yet the mechanisms involved remain unclear. Two major isoforms of Aβ associated with AD are Aβ40 and Aβ42, the latter being more toxic and prone to form oligomers. Here, we took a systems biology approach to study two humanized yeast AD models which expressed either Aβ40 or Aβ42 in bioreactor cultures. Strict control of oxygen availability and culture pH, strongly affected chronological lifespan and reduced variations during cell growth. Reduced growth rates and biomass yields were observed upon Aβ42 expression, indicating a redirection of energy from growth to maintenance. Quantitative physiology analyses furthermore revealed reduced mitochondrial functionality and ATP generation in Aβ42 expressing cells, which matched with observed aberrant mitochondrial structures. Genome-wide expression level analysis showed Aβ42 expression triggered strong ER stress and unfolded protein responses. Equivalent expression of Aβ40, however, induced only mild ER stress, which resulted in hardly affected physiology. Using AD yeast models in well-controlled cultures strengthened our understanding on how cells translate different Aβ toxicity signals into particular cell fate programs, and further enhance their potential as a discovery platform to identify possible therapies.